Towards the synthesis of anthecularin and spirocyclic oxindole alkaloids - Almutaleb, Arabya (2017)
Chapter One. Anthecularin is a new antimalarial sesquiterpene lactone, which was iso-lated from Anthemis auriculata. It originates from Asteraceae, the fami-ly of plants which produce the artimisinin that is known as an antima-larial compound. It possesses inhibitor activity towards PfFabG and PfFabI enzymes, and also shows an antitrypanosmal effect on primary mammalian cells without any toxicity. Anthecularin is a minor sesquiterpene with a novel ring system. The stereochemistry of this new sesquiterpene lactone skeleton indicated the existence of fused seven-and six-membered rings. Herein our current study is focused on the biomimetic synthesis of anthecularin. Our strategy proposes the formation of this natural prod-uct utilizing an intramolecular Diels-Alder cycloaddition in a new biomi-metic pathway inspired by the proposed biogenesis route of anthecular-in. Starting from 2-methacrolein as a readily available material to pro-duce ester through Wittig-Horner reaction, followed by reduction of the ester product. Subsequently the primary alcohol undergoes nucleophilic substitution yielded the propargyl ether, the precursor for the carbocy-clization reaction, which will be followed by oxidation of the cyclic lac-tone after protection of the alcohol. But the carbocyclization reaction did not work, and this prompted us to propose another retrosynthesis route. Chapter Two. This chapter describes the development of a novel route to access the total synthesis of spirocyclic tetrahydroindolizines, featuring a 1,2-dihydropyridine, that may finally be transformed into alkaloid-like indolizidines. The key reaction in this innovative approach is the 1,3-dipolar cycloaddition between pyridinium stabilised ylides and different electrophilic alkenes to generate spirocyclic dihydropyridines as single diastereoisomers with excellent diastereoselectivity. The Introduction introduces related indolizidine natural products such as rhynchophylline, isorhynchophylline, mitraphylline and isometraphylline. This section also reports on development in the field of 1,3-dipolar cycloaddition chemistry, with particular emphasis on the cycloaddition chemistry of pyridinium and related ylides. The Result and Discussion section is divided into three parts. Part I describes model study towards the synthesis of butenolides. Part II describes generation of pyridinium ylides from pyridinium salts in the presence of a variety of dipolarophiles. Further to this, the synthesis of a variety of dipolarophiles is also described. These were then employed in 1,3-dipolar cycloadditions, to achieve tetrahydroindolizines in good yield with excellent diastereoselectivity. The final part describes modification of the 1,2-dihydropyridine ring. Ultimately, expansion of the scope of the reduction reactions is described and opportunities for further developments are discussed. The Experimental part describes all procedures by which compounds disclosed in this thesis were synthesised. Furthermore, full spectroscopic data and characterisation is provided.